Growth Effect of Fiscal Policy in Dependent Natural Resources Countries: Case of a Monetary Union - Nkemgha, Guivis Zeufack; Moumie, Eric Mouchili (Asian Journal of Economic Modelling, 2020)
This paper contributes to the understanding of the other neglected effects of fiscal policy by analyzing how it affects economic growth in developing countries over the period 1980–2014.The empirical evidence is based on a Pooled Mean Group approach. With the panel of dependent natural resources countries that all are members of a Central Africa Economic and Monetary Community (CEMAC), the results show that fiscal policy measured as budget deficit has a positive and significant effect on growth in the short-run while it has a negative and significant effect on economic growth in the long run. The results of a short-run country effect analysis show the effectiveness of fiscal policy in all the countries of the union with an important effect in Equatorial Guinea and the less effect in Cameroon. There for, it would be important for the governments of these countries to diversify their economy, increase the share of manufacturing exports in their total exports and finally rigorously manage their public spending.